Comparison of line fishing catches after and before installed the fish agregating device(FAD’s) - Muhammad Muammar; Arthur Brown; Pareng Rengi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
For purpose to compare line fishing catches, which its were set close at FAD’s device and without FAD’s. Series fishing ctivities were carried out at fishing ground with FAD’s and without FAD’s during July 3rd -13th, 2013 in Teluk Rhu village, North Rupat district, Bengkalis regency, Indonesia. The result show that the composition and number of line fishing catches was signficatly different from T test to the weight of fish Thit = 5.37> Ttab = 1.833, this means Thit> Ttab, Ho is rejected and Hais accepted.with FAD’s and without FAD’s. The line fishing catches by FAD’s  was caugth 1.3 kg (3 individuals) snapper, 0.9 (3 individuals) groupers and 0.4 kg (1individual) puffer fish. While, the line fishing catches without FAD’s was 8 kg (5 individuals)  groupers, 3.1 kg (4 individuals) snappers, 4.6 kg (3 individuals) stingrays, 2.6 kg (3 individuals) croakers and 6 kg (3 individuals) spines.   Keywords: Fish agregating device(FAD’s), line fishing, Teluk Rhu village